2011
DOI: 10.1128/aem.02974-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Five RNA Helicases in the Adaptive Response of Bacillus cereus ATCC 14579 Cells to Temperature, pH, and Oxidative Stresses

Abstract: In this study, growth rates and lag times of the five RNA helicase-deleted mutants of Bacillus cereus ATCC 14579 were compared to those of the wild-type strain under thermal, oxidative, and pH stresses. Deletion of cshD and cshE had no impact under any of the tested conditions. Deletion of cshA, cshB, and cshC abolished growth at 12°C, confirming previous results. In addition, we found that each RNA helicase had a role in a specific temperature range: deletion of cshA reduced growth at all the tested temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…The latter finding is consistent with results obtained with Bacillus cereus: the deletion in the corresponding cshA homolog results in a severe growth defect at lower temperatures in this species as well (19,20). A further analysis of the CshA and CshB homologs of B. cereus revealed that the RNA helicases are also required for growth at a basic pH and under oxidative conditions (21).…”
supporting
confidence: 79%
“…The latter finding is consistent with results obtained with Bacillus cereus: the deletion in the corresponding cshA homolog results in a severe growth defect at lower temperatures in this species as well (19,20). A further analysis of the CshA and CshB homologs of B. cereus revealed that the RNA helicases are also required for growth at a basic pH and under oxidative conditions (21).…”
supporting
confidence: 79%
“…Understanding the mechanisms behind tolerance to stresses caused by food processing, additives, preservatives, sanitizers, and disinfectants may provide new insights into the control of L. monocytogenes in the food chain. In this study, the role of DEAD-box RNA helicase-encoding genes, so far linked mainly to cold stress tolerance of bacteria (4,7,11,37,(43)(44)(45)59), in tolerance of L. monocytogenes to various stress conditions the bacterium may meet in the food chain was examined. Single deletions of the putative DEAD-box RNA helicase-encoding genes lmo0866 and lmo1450 were found to significantly alter the tolerance of L. monocytogenes EGD-e to heat, alkali, ethanol, and oxidative stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, DEAD-box proteins were linked with cold stress tolerance in L. monocytogenes (4,37), Bacillus subtilis (25), Bacillus cereus (44), Escherichia coli (11), and Yersinia enterocolitica (43) by mutational analyses. DEAD-box RNA helicases also contribute to heat, alkali, and oxidative stress tolerance in B. cereus (45), whereas in the anaerobic Clostridium perfringens, a DEAD-box protein was associated with decreased tolerance to oxidative stress (7). In addition, exposure to salt and light resulted in altered transcription of the DEAD-box RNA helicase gene in the cyanobacterium Synechocystis sp.…”
mentioning
confidence: 99%
“…Also, its B. subtilis orthologue, YfmL, is an RNA helicase that is not well characterized and is probably not part of the RNA degradosome, given that it was not able to interact with RNA degradosome components or other helicases in a bacterial two-hybrid system assay (38). The lmo1722 orthologue cshC in B. cereus was among three RNA helicase genes out of five that were required for cold growth and involved in adaptation to several stress conditions (50,51). Lmo1722 has a core region similar to those of other DExD-box RNA helicases but also harbors a unique lysine-rich 72-aminoacid-long C terminus that is not present in the B. subtilis orthologue YfmL (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies have focused on the roles of these RNA helicases in vitro and not in their natural context in vivo (8,10,40,49). One exception is Bacillus cereus, where the physiological functions of five RNA helicase genes were examined with regard to their roles in cold growth and response to various stresses (50,51). In this study, we investigated the function of an RNA helicase in a cold-growing bacterium, L. monocytogenes.…”
mentioning
confidence: 99%